Los estilos de crianza de los hijos y las conductas desadaptativas en adolescentes de la unidad educativa de producción Martha Bucaram de Roldos del cantón Yanzatza, provincia de Zamora Chinchipe, período 2014 – 2015 - Guayllas Macas, Andrea Cruselina (2015)
The way in that parents Exchange with their sons feel in the basis for their social and emotional development in the future of their sons or daughters. So that parents generate a meaningful behavior children influence. The purpose of this study. Analyze the influence the growth children in a wrong behavior in teenagers. Materials and methods. It was a descriptive study, in a sample of 173 students at the same Educative Unit Martha Bucaram de Roldos de Yanzatza city afternoon section. It was applied in a survey, the Embu 89 scale and the quiestionnaire of in a wrong behavior results for it was the 72.25 % it was manifested in the ways of breeding executed by their parents that have of overprotection and the 62.43% has a punishment so that 57.80% shows a reproval manifest. The total of researching student population the 94.79% shows a wrong behavior in low levels.It keeps aggressive and crime attitudes the 98.84 consume legal and illegal drugs .Conclusions The breeding overprotecting styles and the use of punishment and reproval actions influences in the wrong behavior in teenagers It allows the appearance of troubles such as rebelliousness and consume substances.